Rehabilitasi Perumahan dan Permukiman Swadaya Penunjang Wisata Berbasis Kelayakan Huni di Pesisir Pantai Tanjung Bayang Makassar - Fauziah Ahmad Misbahuddin; Shirly Wunas; Mimi Arifin (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2018)
The development of the function of private homes into rental homes in the coast of Tanjung Bayang tends not to pay attention to the standards of building feasibility and life eligibility for residents. This study aims to explain the physical condition of self-help housing and settlement to support tourism related to life feasibility on the coast of Tanjung Bayang Makassar. The data used are primary data that obtained from observations, interviews, literature reviews, laws on housing and settlements and data from the statistical center of the city of Makassar. Data analysis uses qualitative, quantitative and comparative descriptive. Data is presented in the form of numerical values ​​on a continuum scale and calculation of percentages in frequency tables using the IPA method. The results of the study show that the conditions of the self-help housing and settlement in the coast of Tanjung Bayang Makassar has not fulfilled the requirements as a decent tourist residence. The safety aspects of the house buildings, space and window opening areas, as well as the completeness of facilities and infrastructure, such as the installation of electricity networks, availability of clean water, drainage facilities, landfills, and sewage systems are not according to the standards of eligibility for life and visit. The proposed rehabilitation concept includes the direction of the concept of structure and material of the house conctruction, space and window opening area and the utility and sanitation.